(untitled) (Research, Society and Development, 2021)
Covid-19 is an infectious disease caused by the SARS-CoV-2 coronavirus that has resulted in a global pandemic. Its main mechanism of entry into cells is through the angiotensin-2 converting enzyme (ACE-2) and the elderly and those with chronic non-communicable diseases (NCDs) are part of the risk group, including chronic kidney disease (CKD). The objective was to characterize the sample of individuals reported with Covid-19 and CKD, according to clinical and demographic characteristics. Quantitative, cross-sectional study, with retrospective data, obtained through a secondary database, from the e-SUS NOTIFICA system, from March 2020 to December 8, 2020. For the period analyzed, the total number of notifications was of 992,911 individuals, being 110,908 tested positive. A descriptive analysis was performed and only patients with a confirmed diagnosis of Covid-19 were included. Thus, it was concluded that, among the total of positive analyzed, the majority were male (46.2%), with a mean age of 41.42 years and of these, 445 had CKD. Still, of the 110,908 cases, 52.4% had some type of symptom characteristic of Covid-19. The most used test for diagnosis was the Rapid Test – Antibody (93.3%). For patients with CKD and Covid-19, there was a predominance of females (53.0%), the mean age was 53.71 years, the majority symptomatic (59.3%), with the diagnosis confirmed by the Rapid Test - Antibody (86.5%).